2010
DOI: 10.1093/mp/ssq005
|View full text |Cite
|
Sign up to set email alerts
|

Plant Phosphatidylcholine-Hydrolyzing Phospholipases C NPC3 and NPC4 with Roles in Root Development and Brassinolide Signaling in Arabidopsis thaliana

Abstract: Phosphatidylcholine-hydrolyzing phospholipase C (PC-PLC) catalyzes the hydrolysis of phosphatidylcholine (PC) to generate phosphocholine and diacylglycerol (DAG). PC-PLC has a long tradition in animal signal transduction to generate DAG as a second messenger besides the classical phosphatidylinositol splitting phospholipase C (PI-PLC). Based on amino acid sequence similarity to bacterial PC-PLC, six putative PC-PLC genes (NPC1 to NPC6) were identified in the Arabidopsis genome. RT-PCR analysis revealed overlap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 83 publications
3
83
1
Order By: Relevance
“…23 In tobacco cell cultures, treatment with brassinolide raises the DAG content within 15 min through the elevation of PC/PLC activity in a concentration-dependent manner; at the same time the size of the PA pool is not significantly increased. 24 The DAG content of Dunaliella salina cells is rather high in comparison with most animal tissues, particularly in the chloroplast and plasma membrane. When confronted with osmotic shock, the plasma membrane DAG content increases markedly to a level sufficient to consider DAG to be a genuine potential secondary messenger in PLC-mediated signal transduction.…”
Section: Increasing Evidence For Dag Acting As a Signaling Molecule Imentioning
confidence: 99%
“…23 In tobacco cell cultures, treatment with brassinolide raises the DAG content within 15 min through the elevation of PC/PLC activity in a concentration-dependent manner; at the same time the size of the PA pool is not significantly increased. 24 The DAG content of Dunaliella salina cells is rather high in comparison with most animal tissues, particularly in the chloroplast and plasma membrane. When confronted with osmotic shock, the plasma membrane DAG content increases markedly to a level sufficient to consider DAG to be a genuine potential secondary messenger in PLC-mediated signal transduction.…”
Section: Increasing Evidence For Dag Acting As a Signaling Molecule Imentioning
confidence: 99%
“…These genes can be subdivided into two groups based on homology, with NPC1, NPC2 and NPC6 forming one group, and NPC3, NPC4 and NPC5 falling into the second (Wimalasekera et al, 2010). NPC1 and NPC2 are located on chromosome I and II, respectively, with the remaining genes found on chromosome III.…”
Section: Plc Gene Family Classification and Domain Structurementioning
confidence: 99%
“…All of the Arabidopsis NPCs possess three conserved domains of unknown function; the first NPC subgroup also contains a putative secretory sequence at the N-terminus (Nakamura et al, 2005). In contrast, the three nonsecreted NPCs posses a potential zinc finger motif at their C-termini (Wimalasekera et al, 2010), but the importance of this region has not yet been demonstrated.…”
Section: Plc Gene Family Classification and Domain Structurementioning
confidence: 99%
“…A similar trend was observed in NPC4, but was induced to a lesser extent. GUS-reporter expression analysis showed that NPC4 is expressed in immature anthers, which suggests a role of NPC4 in anther development [95]. Floral-organspecificity study in mature flowers showed that NPC6 is highly expressed in pistils [11].…”
Section: Phospholipase C (Plc)mentioning
confidence: 98%
“…Tissue specificity of their expression has been examined by RT-PCR [94,95]. NPC5 is highly specific to flowers and NPC4 is expressed highly both in flowers and siliques.…”
Section: Phospholipase C (Plc)mentioning
confidence: 99%